Comparison of two new tests for rapid diagnosis of respiratory syncytial virus infections by enzyme-linked immunosorbent assay and immunofluorescence techniques. - Freymuth, F (1986)
The sensitivity and the specificity of two new commercial reagent tests, an indirect fluorescent antibody test (FAT) with a mouse monoclonal antibody (MAb) against respiratory syncytial virus (RSV) and an enzyme-linked immunosorbent assay (ELISA) RSV antigen detection kit, were determined by a comparison of results from these tests with those of tissue culture isolation and an indirect FAT with bovine polyclonal antibody (BPA). Of 251 nasal aspirates from infants with suspected RSV infection, positive results were found for 99 (39%) by the FAT-MAb, 93 (37%) by the FAT-BPA, and 87 (35%) by the ELISA; 69 of 240 (29%) were positive by cultures. The FAT-MAb was a more sensitive technique than cultures, with 87% sensitivity for the FAT-MAb and 84% for the ELISA. It was also more sensitive than the FAT-BPA, with 97% sensitivity for the FAT-MAb and 85% for the ELISA. This could be caused only by the distinctive volume of suspended specimens used in these tests. Of 171 negative culture specimens, positive (but not false-positive) results were found for 18% by the FAT-MAb and for 12% by the ELISA. Inversely, 13% of 69 culture positive specimens were FAT-MAb negative and 16% were ELISA negative, emphasizing the importance of tissue cultures for the maximum recovery of RSV, as well as for detection of other respiratory viruses. The FAT-MAb and ELISA were easy to perform and interpret, thus facilitating wider use.